Penerapan Activity Based Costing System Sebagai Dasar Penentuan Harga Sewa Room Karaoke (Studi Kasus Pada NAV Karaoke Keluarga Cabang Braga Citywalk) - Dani Permana, Dani Permana; Gunardi, Gunardi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The purpose of this research is to find out the comparison of the cost of renting karaoke rooms used by NAV Karaoke Management with the cost of goods using the Activity Based Costing System that will be used in this research, so that the results of the comparison can be known using this method. This Activity Based Costing System is worthy and relevant to be used in finding out karaoke room rental prices or it is not quite fitting for the current situation. Descriptive - qualitative technique is used in this study so that researchers can come directly to the related research object, that is NAV Karaoke Braga Citywalk branch, to acquire the data and information needed with a case study approach. The analysis that is used is a comparative analysis, meaning that the researcher has intention to compare the price set by NAV management with the cost calculated using the Activity Based Costing System method with a description of the discussion. The results of this study found a quite significant difference between the cost of goods set by NAV itself and the cost of goods calculated based on calculations using the Activity Based Costing System method, the description of the discussion shows the difference in prices for each type of room available in the current three-month period.